Designing authentic simulations in ROSE and EBUS for undergraduate laboratory medicine students. (29th April 2020) - Miranda, Alina; Kelly, Alison; Williams, Vincent; Kelly, Michelle
Abstract : Introduction: Simulation-based education (SBE) has successfully been implemented in several healthcare professions, more so in the fields of medicine and nursing. Laboratory medicine courses prepare medical scientists for employment in pathology laboratories typically via a staged training regime. Laboratory techniques related to the diagnostic disciplines are introduced to students in a graduated fashion over time for the development of professional skills and technical competencies. For students specialising in diagnostic cytology, there are continual changes to the scope of practice of scientists in industry that require advanced training at undergraduate level to meet expectations of contemporary laboratory testing. Methods: The National Health Education and Training in Simulation (NHET-Sim) framework was applied to create and deliver bespoke simulations for laboratory medicine students. This paper outlines the steps taken, including working with actors and industry partners, to create simulations which contextualise the pressures and team interactions during diagnostic procedures. Findings: Supported by a range of expertise and personnel, five laboratory medicine simulations were developed and delivered to final year students. Details of the steps taken and range of scenarios are included for sharing and discussion. Discussion: SBE can contribute positively to student confidence in communication at interdisciplinary and interprofessional levels in ways that can be essential to successful patient management. Understanding that cytology has now evolved to become part of a multidisciplinary approach to patient-centred care will improve the overall patient outcome and experience to personalised medicine. Conclusion: This paper demonstrates how a high-fidelity SBE scenario can test students' decision-making around technical, clinical and diagnostic competencies in a complex investigation that they would likely experience in industry.